Glucose Isomerization and Epimerization over Metal‐Organic Frameworks with Single‐Site Active Centers. Issue 7 (28th February 2019) - Luo, Qun‐Xing; Zhang, Yuan‐Bao; Qi, Long; Scott, Susannah L.
Abstract: Regulating reaction pathway of glucose isomerization and epimerization is essential for production of high‐fructose corn syrup and rare sugars. Herein, we show a molecular‐level observation on glucose transformation using metal‐organic frameworks (MOFs) with single‐site active centers (SSACs) as heterogeneous catalysts. It is found that Lewis acidic Cr (III) sites of MIL‐101 prefer to catalyze glucose‐to‐fructose isomerization in either water or methanol solvent. Elevating reaction temperature can promote glucose‐to‐mannose epimerization but without intramolecular carbon shift. The Lewis acidic Zr (IV) sites of UiO‐66 can catalyze glucose isomerization and epimerization in aqueous media simultaneously, where glucose‐to‐mannose epimerization proceeds by way of intramolecular carbon‐skeleton rearrangement (C‐1 and C‐2), following the cleavage of the bond between C‐2 and C‐3 and formation of new bond between C‐1 and C‐3. It is proposed that the difference in catalytic behavior might be related to the polarizability of SSACs and particularly to their local coordination environment. Abstract : The great carbon shirt : Glucose isomerization and epimerization over metal‐organic frameworks with single‐site active centers were investigated by isotope labelling and NMR spectroscopy. The molecular‐level observation shows that glucose transformation is dependent on nature of single‐site active centers.